A remarkable new plant bug genus and species (Hemiptera, Heteroptera, Miridae, Deraocorinae) from the Australian wet tropics - Hosseini, Reza; Cassis, Gerasimos (Zootaxa, 2017)
A new genus and new species of deraeocorine plant bug, Kalamemiris gen. nov. and Kalamemiris collessi sp. nov., is described from Australia. Illustrations of male genitalia, scanning electron micrographs of key characters of the male and female habitus, as well as male genitalic characters are provided. The diagnosis of the new genus is made in comparison to other deraeocorines of the Australian biogeographic region.